Foundations for the Design of Mechanisms to Fostering Liquidity in the Secondary Spectrum Market in Brazil (Law, State and Telecommunications Review, 2020)
Purpose ”“ The secondary spectrum market is an innovation within the Brazilian regulatory and legal framework introduced by the Law nº 13.879/2019. Once in operation, it might allow allocative and productive efficiency gains for spectrum as well as to enhance competition in the provision of telecommunications services, particularly in regions with lower economic attractiveness. The objective of this study is to debate the foundations of the mechanism design to foster the secondary spectrum market liquidity in Brazil.Methodology/approach/design ”“ To this end, it is introduced three general mechanisms. The first deals with a laissez-faire approach without regulatory intervention. Then, a brokerage mechanism, widely used in the telecommunications wholesale market, and established on transparency instruments and cost oriented prices is discussed. Finally, a mechanism of License Shared Access with domestic meaningful incentives is assessed.Findings ”“ Results highlight the characteristics and shortcomings of each mechanism. The licensing-based mechanism with incentives displays a relative advantage over the other models.